2022
DOI: 10.3390/cancers14246133
|View full text |Cite
|
Sign up to set email alerts
|

Sialyltransferase Inhibitor Ac53FaxNeu5Ac Reverts the Malignant Phenotype of Pancreatic Cancer Cells, and Reduces Tumor Volume and Favors T-Cell Infiltrates in Mice

Abstract: Hypersialylation is a feature of pancreatic ductal adenocarcinoma (PDA) and it has been related to tumor malignancy and immune suppression. In this work, we have evaluated the potential of the sialyltransferase inhibitor, Ac53FaxNeu5Ac, to decrease tumor sialoglycans in PDA and to revert its malignant phenotype. Sialoglycans on PDA cells were evaluated by flow cytometry, and the functional impact of Ac53FaxNeu5Ac was assessed using E-selectin adhesion, migration, and invasion assays. PDA tumors were generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In a study on pancreatic ductal adenocarcinoma, treatment with Ac 5 3FaxNeu5Ac resulted in the inhibition of the tumor cell production of α2,3-sialic acid and SLe X -modified glycans, leading to reduced adhesion of tumor cells to selectin. Subsequent animal experiments demonstrated that sialic acid inhibition significantly modified the composition of immune cells in the tumor microenvironment by increasing the proportion of CD8 + cells and NK cells, which facilitated the restoration of tumor immune surveillance [ 153 ]. However, the use of 3Fax-Neu5Ac as a global inhibitor of sialyltransferase may affect sialic acid metabolism in other normal organs and has been shown to be toxic to the liver and kidneys when used in large amounts in vivo [ 154 ].…”
Section: Opportunities For Cancer Treatment Via the Removal Of Sialyl...mentioning
confidence: 99%
“…In a study on pancreatic ductal adenocarcinoma, treatment with Ac 5 3FaxNeu5Ac resulted in the inhibition of the tumor cell production of α2,3-sialic acid and SLe X -modified glycans, leading to reduced adhesion of tumor cells to selectin. Subsequent animal experiments demonstrated that sialic acid inhibition significantly modified the composition of immune cells in the tumor microenvironment by increasing the proportion of CD8 + cells and NK cells, which facilitated the restoration of tumor immune surveillance [ 153 ]. However, the use of 3Fax-Neu5Ac as a global inhibitor of sialyltransferase may affect sialic acid metabolism in other normal organs and has been shown to be toxic to the liver and kidneys when used in large amounts in vivo [ 154 ].…”
Section: Opportunities For Cancer Treatment Via the Removal Of Sialyl...mentioning
confidence: 99%